Study of Temperature Gradient in Burning of Alternative Engine Fuels - M. S. Assad (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives an approximate method for calculation of the temperature at a final stage of fuel-air mixture burning in a closed vessel that is a combustion chamber of the internal combustion engine (ICE). The paper contains calculation of temperature values for various fuel-air mixtures, shows nature of temperature changes and presents analysis of combustion product temperature behaviour modification and analyzed the behaviour in accordance with an initial pressure in the chamber. The paper reveals the fact that a combustion temperature is increasing for all mixtures when an initial pressure in combustion chamber is increased. The hydrogen-air mixture has the highest combustion temperature among investigated mixtures and products of propane conversion have the lowest one.The Maxe-effect has been investigated in combustion of hydrogen-air mixture and design formulaes have been obtained. Calculation of temperature difference of the first and last portions of combustion products has been made with due account of the Maxe-effect.The proposed approximate method for calculation of temperatures indices in the various zones of combustion chamber in view of the Mach effect makes it possible to forecast thermodynamic nature of combustion process while using alternative engine fuels for internal combustion engine.